A Analysis of UHT Diamond Milk Supplier Selection With Analytical Hierarchy Process (AHP) Method cafe Milkyway Coffe & Milk In Berau Regency, East Kalimantan: Pemilihan Supplier - Hasto Wisnugroho, Anthonius Dhinar (SAINTEKBU, 2022)
Every business sector certainly wants consistency in production results, this can be realized through collaboration with raw material providers or suppliers who can ensure the consistent availability of raw materials because the production of raw materials is very vital. Therefore, it is necessary to have a good raw material procurement system and supplier selection so that the production process can run smoothly. Milkyway Cafe is the first pioneering UKM of beverage and food business in Berau Regency, East Kalimantan which has a special characteristic of beverage products made from milk which are liked by many customers, especially teenagers, children, and families. There are problems experienced when selecting suppliers who provide raw materials for UHT milk because there are several factors to consider, namely price, delivery, service, and accuracy of quantities. The sample of the research is the owner of the business that regulates the procurement of UHT milk. The results of the analysis and calculation of the Analytical Hierarchy Process (AHP) using Microsoft Excel stated that the chosen alternative, namely the Kompas with a weight value of 0.46, was superior to the Simpang Utama with a weighted value of 0.34 and the Tops Jaya with a weighted value of 0.20. The main factors that are prioritized in the selection of suppliers at Milkyway are service criteria with a weight value of 0.18, the accuracy of the number of goods with a weight value of 0.15, prices with a weight value of 0.08, and delivery with a weight value of 0.06.